ANALISIS KOMPARATIF METODE MOORA DAN WEIGHTED PRODUCT UNTUK PRIORITAS PENANGANAN BALITA STUNTING - Nungsiyati, Nungsiyati; Sofy, Ahyani; Muslihudin, Muhamad (Institut Bakti Nusantara, 2025)
Stunting in toddlers is a public health issue that still requires significant attention. Stunting is a long-term nutritional problem recognized as a national priority. Based on data from the Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting reflects a high risk of developmental disorders that affect a child's future. This study was conducted with the aim of identifying priorities for handling stunted toddlers by comparative analysis of two Decision Support System (DSS) methods, namely MOORA and Weighted Product (WP). This study used a quantitative approach involving interviews, observations, and literature studies conducted in the working area of the Bandung Baru Community Health Center (UPT). Ten toddler alternatives were analyzed based on five criteria: nutritional status (W/A), physical growth (H/A), mid-upper arm circumference (LILA), age, and vitamin A intake. The technical implementation included a normalization process, weighting, preference calculations using the MOORA and WP methods, and sensitivity testing to weight changes. The research findings indicate that both methods produced the highest stable ranking for alternative A9, while the lowest rankings were obtained for A1, A7, and A8. Sensitivity tests showed that the WP method experienced a 2% change in results, while MOORA experienced a 7% change, indicating that WP was more consistent with weight changes. This research is expected to assist community health centers and related institutions in prioritizing stunting interventions more objectively, efficiently, and responsively to policy changes.